Global gene expression analysis of pigeonpea with male sterility conditioned by A2 cytoplasm. Issue 3 (8th September 2021) - Bohra, Abhishek; Prasad, Gandam; Rathore, Abhishek; Saxena, Rachit K; Naik SJ, Satheesh; Pareek, Shalini; Jha, Rintu; Pazhamala, Lekha; Datta, Dibendu; Pandey, Gaurav; Tiwari, Abha; Maurya, Alok Kumar; et al.
Abstract: Cytoplasmic male sterility(CMS), a maternally inherited trait, provides a promising means to harness yield gains associated with hybrid vigor. In pigeonpea [ Cajanus cajan (L.) Huth], nine types of sterility‐inducing cytoplasm have been reported, of which A2 and A4 have been successfully deployed in hybrid breeding. Unfortunately, molecular mechanism of the CMS trait is poorly understood because of limited research invested. More recently, an association between a mitochondrial gene ( nad7 ) and A4 ‐CMS has been demonstrated in pigeonpea; however, the mechanism underlying A2 ‐CMS still remains obscure. The current investigation aimed to analyze the differences in A2 ‐CMS line (ICPL 88039A) and its isogenic maintainer line (ICPL 88039B) at transcriptome level using next‐generation sequencing. Gene expression profiling uncovered a set of 505 genes that showed altered expression in response to CMS, of which, 412 genes were upregulated while 93 were downregulated in the fertile maintainer line vs. the CMS line. Further, gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and protein–protein interaction (PPI) network analyses revealed association of CMS in pigeonpea with four major pathways: glucose and lipid metabolism, ATP production, pollen development and pollen tube growth, and reactive oxygen species (ROS) scavenging. Patterns of digital gene expression were confirmed by quantitative real‐time polymerase chain reaction (qRT‐PCR) of six candidate genes. This study elucidates candidate genes and metabolic pathways having potential associations with pollen development and male sterility in pigeonpea A2 ‐CMS. New insights on molecular mechanism of CMS trait in pigeonpea will be helpful to accelerate heterosis utilization for enhancing productivity gains in pigeonpea. Core Ideas: RNA‐seq was performed on unopened floral buds of isogenic pigeonpea lines. A total of 505 differentially expressed genes were identified. GO and pathway‐level analysis associated CMS occurrence with four major pathways. PPI network analysis revealed a set of 15 hub genes The study provides a functional genomics resource to understand male sterility trait in plants.